Online Marketing Strategy and Customer Loyalty in E-commerce-Based Asian Business: The Case of Tokopedia and Shopee - Eri Mardiani; Judijanto, Loso; Syamsuri, Syamsuri; Sufa, Siska Armawati (West Science Journal Economic and Entrepreneurship, 2023)
This research investigates the dynamic interactions between online marketing strategies, customer loyalty, and e-commerce business success in Asian markets, with a particular focus on the Tokopedia and Shopee platforms. Quantitative analysis was conducted with a diverse sample, taking into account demographic factors such as age, gender, and geographical distribution. The measurement model assessment confirmed the reliability and validity of the survey instrument, providing a solid foundation for the subsequent analysis. Evaluation of the structural model revealed a significant direct impact of online marketing strategies on customer loyalty, which in turn positively impacts e-commerce business success. The model fit assessment, R-Square value, and hypothesis testing results collectively underscore the robustness and significance of this study's findings. The implications of this study extend to businesses, marketers, and policymakers looking to navigate the competitive landscape of Asian e-commerce.